Balansreceptet: Konsten att hantera klimakteriet i självhjälpslitteraturens hormonberättelser - Berg, Linda; Lundgren , Anna Sofia; Jönsson , Maria (Kvinder, Køn & Forskning, 2023)
In recent years, menopause as a phase of transition has received great media attention in Sweden, not only in terms of the cessation of menstrual periods, but specifi cally with a focus on hormonal changes in the longer period of time during which female bodies undergo adjustment. In books such as Hormonstark [Hormone strong] (2020), Perimenopower (2018) and Livet med klimakteriet [Life with Menopause] (2020), the stressed reader in mid-career can get knowledge, tips, ideas and inspiring stories about how to deal with the fl uctuating hormones that are said to affect the body during menopause. In this article, we take a poststructuralist feminist perspective on the narratives of hormones and body control in the above mentioned three examples of self-help literature. The aim is to explore how this type of literature represents women’s menopause and hormonal bodies in a broader sense, and how women are in relation to this discourse. The results show that, although hormone narratives may have feminist potential, they primarily represent menopause as an individual rather than a structural matter. The result also display a close resemblance between hormone narratives and contemporary biocapitalism with the aging female body as a lucrative threat.